Elizabeth Moraes Gonçalves, José Antonio Bonato. A mídia e a educação científica: uma... A mídia e a educação científica: uma discussão sobre a cobertura da reforma do código florestal brasileiro pela Folha de S.Paulo - Elizabeth Moraes Gonçalves; José Antonio Bonato (Universidade Estadual Paulista Júlio de Mesquita Filho, 2012)
The text aims to lead to a reflection on the importance of scientific knowledge for decision-making in different sectors of society and the commitment of media not to restrict itself to factual coverage, but to contribute to the educational process. The reform of the Brazilian Forestry Code in 2011 occupied large spaces both in Congress and the media. Brazilian Deputies approved the proposal on the expansion of deforestation without hearing scientists. This measure impacts the Brazilian goal of emissions of gases that enhance the greenhouse effect. The "Folha de S. Paulo" defended in editorials, the change in legislation but only supported in favor of the manifestation of the scientists after the measure had been approved. The society was left out of this discussion, because it was not built a scientific knowledge capable of providing an understanding of the significance of this reform and the environmental consequences that directly affect life on Earth. This article examines the coverage of the "Folha de S. Paulo" of Brazil's Forestry Code reform from the perspective of discourse analysis and concludes that the contract between reader and the newspaper has proved unsuitable, because it was expected more analysis and reflection of issues of such importance.